The 2022 record-high heat waves over southwestern Europe and their underlying mechanism - Jeong-Hun Kim; So-Hyun Nam; Maeng-Ki Kim; Roberto Serrano-Notivoli; Ernesto Tejedor (Weather and Climate Extremes)
Recently, the intensity and frequency of heat waves (HWs) have been increased worldwide. Particularly in 2022, Europe was severely affected by unprecedented HWs, which caused approximately 61,672 deaths and 11,324 deaths in Europe and Spain, respectively. In this study, we investigate the mechanisms of the HWs in southwestern Europe (SWEU) to identify the differences between typical HWs and the extreme HWs that occurred in 2022. Our results showed that the SWEU events in 2022 were strongly related to robust heat domes that developed in the lower troposphere due to high-pressure anomalies especially during two periods (9–18 June and 8–19 July). Analyses of the energy budget and thermodynamic equation revealed the processes underlying the amplification of the heat domes over SWEU during both periods. We also discovered that abnormal atmospheric blocking in the upper troposphere was closely associated with the amplification of the Gulf Stream SST, which caused an atmospheric circulation pattern favorable for the 2022 SWEU-HWs. This was further confirmed by modeling experiments. Therefore, our results emphasize that a Gulf Stream SST amplification can trigger an atmospheric circulation pattern favorable for extreme HWs in SWEU, enhancing our understanding of the mechanism behind extreme HWs. Finally, our findings will help improving the forecasting of SWEU-HWs on a sub-seasonal time scale, as well as future projections in global climate models.